Acceptability of self-administered acupressure for knee osteoarthritis in middle-aged and older adults: A mixed-method secondary analysis - Shu-Cheng Chen; Nicole Nok Leung; Hui-Lin Cheng; Min-Ru Wu; Denise Shuk-Ting Cheung; Jia-Yin Ruan; Jing Qin; Ge Ren; Wing-Fai Yeung (Complementary Therapies in Medicine)
Objectives: To evaluate the acceptability of self-administered acupressure for Knee osteoarthritis (KOA) among middle-aged and older adults. Methods: This is a mixed-method acceptability evaluation was embedded in a randomized controlled trial on self-administered acupressure for KOA. Participants received two 2-h training sessions on self-administered acupressure and were instructed to practice twice daily for 12 weeks. Quantitative data were collected using an acceptability questionnaire (n = 153) and acupressure logbooks (n = 157). Qualitative data were obtained through semi-structured interviews, including post-training (n = 13) and post-intervention focus groups (n = 13), and individual interviews with participants who dropped out (n = 5). Data were analysed using descriptive statistics and framework analysis based on the Theoretical Framework of Acceptability. Results: The intervention had 91.7 % completion rate. Participants rated willingness to attend future sessions at 9.5/10 (SD=0.85). 57.8 % found technique education ''very helpful'' and 81.5 % followed the prescribed routine. Participants reported high overall acceptability of the self-administered acupressure training program, citing its practicality and potential benefits on knee pain, thigh strength, inflammation, and swelling. The minimal time and financial investment required were also appreciated. However, challenges related to personal efforts, time management, pressure from research monitoring, possible adverse events, and uncertainties with acupressure techniques were noted, leading to adherence issues. Participants expressed a need for continuous professional guidance. Conclusion: Self-administered acupressure is highly acceptable to middle-aged and older adults with KOA due to its potential benefits and merits of minimal time and cost. Future research should focus on optimizing intervention implementation by providing professional support and efficient monitoring to address identified challenges.